Functional recovery in patients with nonunion treated with the Ilizarov technique. - Barker, K; Lamb, S; Simpson, A (2004)
There are few reports on function after limb salvage surgery using the Ilizarov technique, and none that document the pattern of recovery or predict when maximum function returns. This prospective, longitudinal study documents the baseline functional abilities of 40 consecutive patients with nonunion of a fracture in the lower limb. Patients were studied for at least two and a half years following the completion of surgery. Function was measured by timed tests of functional performance and by the Toronto Extremity Salvage Score self-reported patient questionnaire. Recovery was slowest in the early stages after removal of the frame and greatest between six months and one year. Statistically significant improvement continued up to, but not beyond two years. This observation has important implications for the length of follow-up incorporated into the rehabilitation programmes for patients, predictions of patient status in regard to compensation and for the design of future studies to evaluate functional outcome.